Dual Functional Capability of Dendritic Cells – Cytokine-Induced Killer Cells in Improving Side Effects of Colorectal Cancer Therapy - Mosińska, Paula; Gabryelska, Agata; Zasada, Malwina; Fichna, Jakub (Frontiers in Pharmacology, 2017)
The aim of cancer therapy is to eradicate cancer without affecting healthy tissues. Current options available for treating colorectal cancer (CRC), including surgery, chemotherapy or radiotherapy, usually elicit multiple adverse effects and frequently fail to completely remove the tumor cells. Thus, there is a constant need for seeking cancer cell-specific therapeutics to improve the course of cancer therapy and reduce the risk of relapse. In this review we elaborate on the mechanisms underlying the immunotherapy with dendritic cells (DCs) and cytokine-induced killer (CIK) cells, and summarize their effectiveness and tolerability available clinical studies. Finally, we discuss the up-to-date combinatorial adoptive anti-cancer immunotherapy with CIK cells co-cultured with DCs that recently showed encouraging efficacy and usefulness in treating malignant disease, including CRC.